The effect of political connections on market performance with financial performance as a mediation variable for companies listed on Indonesia stock exchange (period 2014-2017) - Elviga Cintha Ligita; Muazaroh Muazaroh (Journal of Business & Banking, 2019)
This study aims to examine the impact of political connections on market performance with financial performance as a mediating variable. The sample in this study were non-financial companies listed on the Indonesian stock exchange for the period 2014 to 2017. There were 17 companies that had political connections during the study period. There are 17 comparison companies namely non-politically connected companies that were also used in this study. Market performance is measured using Tobin's Q ratio. Financial performance is measured using ROA and ROE and control variables use company size and leverage. This model uses multiple linear regression. The results shows that political connections have a significant effect on market performance but political connections do not have significant effect on financial performance, and financial performance does not mediate between political connections and market performance.